2016
DOI: 10.1101/pdb.top079921
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Schizosaccharomyces pombe: Sample Preparation, Detection, and Data Interpretation

Abstract: Metabolomics is a modern field of chemical biology that strives to simultaneously quantify hundreds of cellular metabolites. Techniques for metabolomic analysis in Schizosaccharomyces pombe have only recently been developed. Here we introduce methods that provide a complete workflow for metabolomic analysis in S. pombe. Based on available literature, we estimate the yeast metabolome to comprise on the order of several thousand different metabolites. We discuss the feasibility of extraction and detection of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Metabolite standards were purchased from commercial sources (Table S3). Other reagents have been previously described 6,7,43 .…”
Section: Methodsmentioning
confidence: 99%
“…Metabolite standards were purchased from commercial sources (Table S3). Other reagents have been previously described 6,7,43 .…”
Section: Methodsmentioning
confidence: 99%
“…Metabolite standards were purchased from commercial sources (Table S3). Other reagents have been previously described 6,7,43 . Hospital and by the Human Subjects Research Review Committee of the Okinawa Institute of Science and Technology Graduate University (OIST).…”
Section: Methodsmentioning
confidence: 99%
“…We initially investigated metabolomics of a simple model eukaryote, fission yeast (Schizosaccharomyces pombe) using yeast genetic technology to identify and determine metabolite profiles in wild type and mutant cell extracts (Pluskal et al, 2010b) (Pluskal and Yanagida, 2016a) (Pluskal and Yanagida, 2016b). By adapting the software MZmine 2 for metabolite identification (Pluskal et al, 2010a) (Pluskal et al, 2012), we found that metabolomics of fission yeast and humans are surprisingly similar in regard to metabolite composition (Chaleckis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%